2018
DOI: 10.1111/spc3.12408
|View full text |Cite
|
Sign up to set email alerts
|

Affective processes as mediators of links between close relationships and physical health

Abstract: Close relationships are known to predict physical health outcomes. The time has come for a shift toward achieving a better understanding of the underlying mechanisms. One promising group of psychological mechanisms is affective processes, such as discrete emotions, emotion regulation, and affect reactivity. In this paper, we discuss the evidence linking relationship functioning with both the positive and negative valences of each affective process, considering the contributions of different types of close rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 103 publications
5
24
0
Order By: Relevance
“…Wave 1), we show that these links are robust over time. Moreover, the current study is novel in that it links a critically-important relationship construct with a psychological mediator and mortality together in a single prospective investigation, a rare occurrence in longitudinal psychology studies (5051). Although previous research has found evidence that PA reactivity is sometimes linked to longevity (37), a similar pattern did not emerge in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Wave 1), we show that these links are robust over time. Moreover, the current study is novel in that it links a critically-important relationship construct with a psychological mediator and mortality together in a single prospective investigation, a rare occurrence in longitudinal psychology studies (5051). Although previous research has found evidence that PA reactivity is sometimes linked to longevity (37), a similar pattern did not emerge in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that relational self‐expansion potential should be associated with better perceived physical health, and that affect should underlie this association. Affective processes have been found to be robust mediating pathways that explain how relationships are linked to health (Farrell, Imami, Stanton, & Slatcher, 2018; Sbarra & Coan, 2018). PA encompasses alert feelings that reflect pleasurable engagement with the environment, whereas NA encompasses distressed feelings that reflect unpleasurable engagement with the environment (Watson, Clark, & Tellegen, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Wave 1), we show that these links are robust over time. Moreover, the current study is novel in that it links a critically-important relationship construct with a psychological mediator and mortality together in a single prospective investigation, a rare occurrence in longitudinal psychology studies (50)(51). Although previous research has found evidence that PA reactivity is sometimes linked to longevity (37), a similar pattern did not emerge in our sample.…”
Section: Discussionmentioning
confidence: 51%